Field Evaluation of Sumilarv® 2MR Efficacy Against Aedes aegypti Larvae in Water-Storage Containers in Thailand - Bhakdeenuan, Payu; Thavara, Usavadee; Sirisopa, Patcharawan; Srivarom, Navy; Kunhachan, Phanukit; Khumsawad, Chayada; Samaimai, Srisuda; Tawatsin, Apiwat (British Journal of Healthcare and Medical Research, 2024)
Vector-borne disease transmission by Aedes mosquitoes, including Dengue, Chikungunya, and Zika fever, is estimated to increase massively worldwide. An alternative strategy for disease control is to limit the vector populations by using a larvicide. This study was initiated to evaluate the residual efficacy of a newly developed larvicide, Sumilarv® 2 MR, against larvae of Aedes aegypti that thrive in water-storage containers under simulated field conditions in Thailand. The Sumilarv® 2 MR, a 5.5 cm diameter resin disc containing 2% (w/w) pyriproxyfen, was used in this study against Aedes aegypti larvae in the simulated field trial method. The discs were immersed in 40L, 80L, and 160L of tap water in water-storage containers (1 piece/container); resulting in 3 different dosages of Sumilarv® 2 MR treatment. The controls were immersed in similar containers filled with tap water but without the disc. Five containers were used for each treatment and the controls. Pupal skins in each container were counted weekly, and the Emergence Inhibition Rate (%IE) was calculated. For the field simulation, half the volume of water in each container was removed weekly and replaced with new tap water for 114 weeks. During the 114 weeks of evaluation, average IE rates of 98.58% ± 1.73, 98.25% ± 2.20, and 97.94% ± 2.55 were observed in the 40L, 80L and 160L containers, respectively. There was no significant difference (p>0.05) in residual efficacy among the three dosages used in this study. Furthermore, the average %IE of all dosages was not less than 96.0%, even at the lowest dosage (160-liter containers) until the last weeks of evaluation. All dosages of Sumilarv® 2 MR in this study provided a high level of larvicidal efficacy (almost 100 %IE) in a water exchange regimen for up to 2 years post-treatment. This could be an effective environmentally friendly device for controlling Aedes aegypti larvae in water-storage containers.